The Influence of Work Discipline and Work Supervision on Employee Performance at PT. Sinar Gloria Abadi, West Bandung Regency - Justinus Octavianus; Joshua Steven; Joshua Gama Oktomega Sumartoyo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The purpose of this study was to determine Work Discipline, Work Supervision on Employee Performance at PT. Sinar Gloria Abadi, West Bandung Regency and knowing the effect of Work Discipline, Work Supervision on Employee Performance at PT. Sinar Gloria Abadi, West Bandung Regency. The research method used is a quantitative method with a descriptive verification approach; the samples were taken for this research are employees of PT. Sinar Gloria Abadi has as many as 64 people. Based on research using the SPSS application, Work Discipline and Work Supervision have a simultaneous effect on Employee Performance. The results of the work discipline variable (X1) and work supervision variable (X2) show a positive influence and can increase the employee performance variable (Y) at PT Sinar Gloria Abadi